A river journey: metaphoric reflection on a study exploring Dialectical Behaviour Therapy – Skills Group with senior nursing students. Issue 4 (4th July 2019) - Schwind, Jasna K.; Beanlands, Heather; McCay, Elizabeth; Martin, Lori Schindel; Wang, Angel He; Fredericks, Suzanne; Newman, Kristine; Santa Mina, Elaine; Aiello, Andria; Rose, Donald
ABSTRACT: By engaging in regular reflective writing and dialogue, individuals puzzle through life events, while nurturing the curiosity for further learning and discovery. In research contexts, reflection that includes creative self-expression augments sense-making of study findings. In our work, we use metaphoric reflection to expand our thinking and understanding of how senior nursing students engage in and respond to Dialectical Behaviour Therapy – Skills Group intervention and the impact this has on their sense of perceived stress and anxiety. We explicate how we, as research team, extended our thinking and understanding of our mixed-method study, using metaphoric reflection approach.